Tax Incentives and Job Creation in the Tourism Sector of Brazil's SUDENE Area. (August 2017) - Garsous, Grégoire; Corderi, David; Velasco, Mercedes; Colombo, Andrea
Highlights: Tax credits are often used by emerging countries to support their tourism industry. Their actual capacity to create jobs in the tourism sector remains to be tested. We study the impact of tax credits on employment in the Brazilian tourism sector. We causally identify an increase of 30% in local employment over eight years. Results call for a better assessment of the efficiency of similar fiscal policies. Summary: In recent decades, a significant number of developing countries have implemented fiscal incentives programs for the tourism industry as part of their regional development policies. The main objective of these programs is to increase local investment and employment, as tourism activities are labor intensive. Little evidence is available, however, to assess the effect of these policies on job creation in emerging markets. In this paper, we analyze a program of fiscal incentives introduced by the Brazilian federal government in the SUDENE area in 2002 and in which tourism firms were eligible to participate. Through a difference-in-difference estimation, we compare the change in the logarithm of local employment in the SUDENE municipalities before and after 2002 to the change in the same outcome in a group of municipalities that were not affected by the program. Although our empirical analysis does not measure the efficiency of a similar fiscal policy, it is the first one in the literature to show its effectiveness. It provides evidence that the fiscal incentives led to a substantial increase in tourism employment in the SUDENE area. We find that, over the period 2002–09, municipal tourism employment was on average 30% higher than in the absence of the intervention. This result is robust and is not the consequence of either displacement effects or job destruction in neighboring municipalities that had not been targeted by the tax incentives. We finally discuss some limitations of our analysis that might open avenues for future research in the field.